Development time, mortality, and bioenergetic responses of larvae of the giant barnacle Austromegabalanus psittacus (Molina 1788) under controlled hatchery conditions of temperature and salinity - Mauricio O. Pineda; Boris A. López; Paulina Gebauer; Kurt Paschke (Aquaculture Reports, 2025)
Barnacle production is a new aquaculture activity, that has developed to a semi-industrial level with extensive cultures in floating systems. However, the mass culture of larvae and juveniles under controlled hatchery conditions have not yet been developed. In this study, the larval development of the giant barnacle Austromegabalanus psittacus (Molina, 1788) was experimentally examined at different combinations of temperature (9, 12, 15, 18, and 21°C) and salinity (20, 24, 28, and 32 PSU). The development time, mortality and metabolism of the larval stages and their influence on the energy of cyprids and recently metamorphosed juveniles were evaluated. Larval development was completed at 9 and 21°C combined with salinities of 28 and 32 PSU. There was 100 % larval mortality at salinity ranges from 20 to 24 PSU. Larval development time was shorter at 21°C /24 PSU (8.50 ± 0.70 days) and longer at 9°C /32 PSU (33.57 ± 2.93 days). Oxygen consumption and ammonium excretion increased with the increase in temperature and reduction in salinity. The lowest accumulated mortalities were observed at 18°C with salinities of 28 and 32 PSU, as were the highest content of lipids and proteins, production levels, and net growth efficiency (K2). The results indicate that the combination of temperature and salinity has a synergetic effect on larval development time, survival, and energy accumulation on A. psittacus larvae. These results establish the basis for the design of protocols for cultivating larvae in hatcheries increasing the predictability of juvenile supplies for industrial-scale production of this species.